2019
DOI: 10.1007/s10964-019-01117-9
|View full text |Cite
|
Sign up to set email alerts
|

Dual Identity Development and Adjustment in Muslim Minority Adolescents

Abstract: Dual identity (e.g., strong ethnic and national identity) is a psychological resource for minority groups, but how it develops during adolescence is less clear. In this 3-wave longitudinal study, a person-oriented approach was used to examine dual identity development in a sample of 2145 Muslim adolescents (MT1 = 15 years, 51% female) in four Western European countries. The results of a growth-mixture model pointed toward four distinct developmental Classes: (1) “Dual identity”, (2) “Separation to dual identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 48 publications
2
31
0
2
Order By: Relevance
“…The other two classes could be described as different kinds of integration, one group where individuals start from separated and move to integrated, and another class where both identifications are moderately high and stable over time. Another study with Muslim adolescents in four Western European countries (Spiegler et al 2019 ) found four different trajectory classes, integrated (both increasing), moving from separated to integrated, moving from assimilated to integrated, and separated (both decreasing).…”
Section: Introductionmentioning
confidence: 99%
“…The other two classes could be described as different kinds of integration, one group where individuals start from separated and move to integrated, and another class where both identifications are moderately high and stable over time. Another study with Muslim adolescents in four Western European countries (Spiegler et al 2019 ) found four different trajectory classes, integrated (both increasing), moving from separated to integrated, moving from assimilated to integrated, and separated (both decreasing).…”
Section: Introductionmentioning
confidence: 99%
“…What we observed, in contrast, was that the Integrated class was very large to begin with but decreased by 15 % points among Turkish-origin and by 25 % points among resettler-origin youth. This decline of integration is surprising given that other studies found that most ethnic minority adolescents develop some form of dual identity over time (Spiegler et al, 2019;Stoessel et al, 2014). To be sure, despite its decline the Integrated class is still the largest class compared to the other classes across all measurement occasions.…”
Section: Transitions Between Classes Over Time and Changes In Class Smentioning
confidence: 82%
“…Both classes were characterized by high stability across time, and when changes occurred, individuals were more likely to transition from high to low integrated than vice versa. However, previous research (e.g., Spiegler et al, 2019) suggests that identification profiles are more varied in German samples.…”
Section: Previous Research On Api Developmentmentioning
confidence: 84%
See 2 more Smart Citations